Estudo hidroquímico do Aquífero Barreiras no Município de Eusébio, Ceará - Oliveira, Rafael Mota de (2017)
The quality of the Barreiras aquifer, which crops out in approximately 66% of the municipality of Eusébio, Ceará, has been considerably compromised due to rapid real estate expansion, the lack of corresponding investments in basic sanitation, and irregularly constructed wells. In order to evaluate groundwater quality, 107 in situ measurements of pH, total dissolved solids (TDS) and electrical conductivity (EC) were carried out and 20 groundwater samples werecollected for physical-chemical and bacteriological laboratory analyses. The results were compared to Ordinance No. 2,914 of December 12, 2011, which establishes the potability standards for human consumption of water. The groundwater analyzed has an average pH of 7.0, but in 21 wells, measurements fell outside the potability standards. Turbidity, hardness, and the concentrations of iron, fluoride, sulfate, nitrite and nitrate are within the standards of potability, although concentrations of chloride in four samples and sodium in five samples exceed the standards. Regarding the microbiological quality of the waters, 65% of the samples present total coliform values indicating contamination from domestic sewage. In the ionic classification, chlorinated waters (45%) predominate, followed by sulphated (40%) and mixed waters (15%) regarding anions, whereas in cations the waters are classified as sodic. According to the US Salinity Laboratory Diagram, the analyzed waters present salinity hazards ranging from medium to high (EC of 250 to 2,250 μS cm-1 at 25 ºC); and, in relation to sodium, present risks range from medium to very strong (SAR – Sodium Adsorption Ratio of 10 to 30).